A Five-Bundle Intervention to Improve Blood Culture Use in a Tertiary Hospital in Romania - Alina-Ioana Popa; Daniela Tălăpan; Gabriel-Adrian Popescu (MDPI AG, 2024)
Objectives: The aims of this study were to evaluate the efficacy of a five-bundle intervention and to decrease the number of cases in which only one set of blood cultures is collected prior to starting antimicrobials. Methods: The study group consisted of the two hospital wards that have the highest collection rate (120 blood cultures/1000 patient days and 121.4 blood cultures/1000 patient days, respectively), and the control group consisted of the other three adult wards. The collection protocol was changed, and a bundle of five measures was introduced: one-on-one discussions with the nurses, 2% chlorhexidine in 70% alcohol for disinfection, ensuring the use of sterile gloves, sterile wipes, a checklist for the materials needed, and a copy of the collection protocol. The impact of these changes was followed over a 5-month period. Results: Prior to the intervention, the contamination rate was higher in the control group (6.5%) versus the study group (4%), p = 0.00578. The before-after analysis revealed a significantly reduced contamination rate in the control group (4.6% vs. 6.5% p = 0.0099), but it was above the one obtained in the study group (3.1% vs. 4%, p = 0.1635). The number of infectious episodes in which one blood culture set was collected decreased significantly in the study group (77/311 vs. 139/456, p = 0.041). Conclusions: The intervention decreased the contamination rate and the number of infectious episodes in which one blood culture set is collected.